2020
DOI: 10.1016/s2468-1253(19)30337-1
|View full text |Cite
|
Sign up to set email alerts
|

Rectal indometacin dose escalation for prevention of pancreatitis after endoscopic retrograde cholangiopancreatography in high-risk patients: a double-blind, randomised controlled trial

Abstract: Background: Although rectal indomethacin (100mg) is effective in reducing the frequency and severity of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis in high-risk patients, the optimal dose is unknown and pancreatitis rates remain high despite its use. The aim of this study was to compare the efficacy of two dose regimens of rectal indomethacin on the frequency and severity of post-ERCP pancreatitis in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…Recently, a large scale multicenter randomized trial was conducted to compare the efficacy of high‐dose regimen (200 mg) and standard‐dose regimen (100 mg) of rectal NSAIDs on the frequency of PEP, and the high‐dose regimen did not appear to offer any advantage over the standard‐dose regimen 17 . This result suggests that the effect of NSAIDs in preventing PEP may not be dose dependent, and if low dose rectal NSAIDs can prevent PEP as well as the standard dose, it is likely to be safer than a standard dose.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large scale multicenter randomized trial was conducted to compare the efficacy of high‐dose regimen (200 mg) and standard‐dose regimen (100 mg) of rectal NSAIDs on the frequency of PEP, and the high‐dose regimen did not appear to offer any advantage over the standard‐dose regimen 17 . This result suggests that the effect of NSAIDs in preventing PEP may not be dose dependent, and if low dose rectal NSAIDs can prevent PEP as well as the standard dose, it is likely to be safer than a standard dose.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the frequency of PEP between the 25 and 50 mg groups as well (9% [2/22] vs. 0% [0/29], p = 0.101). Considering a lower mean body weight of this Japanese population, low-dose 50 mg of rectal NSAID Recently, two randomized clinical trials with dose escalation of rectal indomethacin to 200 mg were reported [38,43]. It was hypothesized that a higher dose might be superior to the existing standard 100 mg dose in PEP prevention.…”
Section: Dose Of Rectal Nsaids: Low Vs Single Vs Double Dosementioning
confidence: 99%
“…It was hypothesized that a higher dose might be superior to the existing standard 100 mg dose in PEP prevention. Split dose administration was performed in both studies: to minimize the potential for adverse events of the higher dose in one study [38], and to potentially lead to a higher peak serum concentration and a more sustained impact on the inflammatory cascade in the second study [43]. In the first trial from Taiwan, which evaluated predominantly average-risk patients, the double dose group received an initial 100 mg about 4 to 5 hours before ERCP and an additional 100 mg immediately after ERCP [38].…”
Section: Dose Of Rectal Nsaids: Low Vs Single Vs Double Dosementioning
confidence: 99%
See 2 more Smart Citations